A new frontier in digital activism: An exploration of digital feminism in Fiji. Issue 3 (1st September 2018) - Brimacombe, Tait; Kant, Romitesh; Finau, Glenn; Tarai, Jope; Titifanue, Jason
Abstract: Social media has become a crucial feature of the Pacific islands in the 21st century, providing people with the means to demand greater accountability and transparency and offering an alternative platform through which to engage in policy processes, dialogue, and debate. Increasing social media access and use has altered the existing media and communications landscape, with implications for mainstream media reporting, censorship, and citizen voice. This paper explores this phenomenon through an examination of the digital activism practices of a group of women's rights activists in Fiji. In doing so, this paper explores how social media is being used as an online platform for information dissemination and debate, as well as the implications this is having "offline" as part of efforts to influence policymaking.